Pacemaker lead infection: echocardiographic features, management, and outcome. Issue 1 (1st January 1999) - Victor, F; De Place, C; Camus, C; Le Breton, H; Leclercq, C; Pavin, D; Mabo, P; Daubert, C
Abstract : Objective: To compare transthoracic and transoesophageal echocardiography (TTE, TOE) in patients with permanent pacemaker lead infection and to evaluate the safety of medical extraction in cases of large vegetations. Methods: TTE and TOE were performed in 23 patients with definite pacemaker lead infection. Seventeen patients without previous infection served as a TOE reference for non-infected leads. Results: TTE was positive in seven cases (30%) whereas with TOE three different types of vegetations attached to the leads were visualised in 21 of the 23 cases (91%). Of the 20 patients with vegetations and lead culture, 17 (85%) had bacteriologically active infection. Left sided valvar endocarditis was diagnosed in two patients. In the control group, strands were visualised by TOE in five patients, and vegetations in none. Medical extraction of vegetations ⩾ 10 mm was performed in 12 patients and was successful in nine (75%) without clinical pulmonary embolism. After 31.2 (19.1) months of follow up (mean (SD)), all patients except one were cured of infection; three died from other causes. Conclusions: Combined with bacteriological data, vegetations seen on TOE strongly suggest pacemaker lead infection. Normal TTE examinations do not exclude this diagnosis because of its poor sensitivity. Medical extraction of even large vegetations appeared to be safe.